2023
DOI: 10.1017/s0014479722000540
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release urea increases soybean yield without compromising symbiotic nitrogen fixation

Abstract: Summary In Brazil, high-yield soybean [Glycine Max (L). Merrill] – corn (Zea mays L.) double cropping system might be nitrogen (N)-limited and additional N fertilization can be beneficial. Early application of N in soybean reduces the symbiotic N fixation (SNF) efficiency and/or establishment. One alternative to avoid SNF impairment is to apply N between the beginning pod (R3) and seed-fill (R5) stages through the use of controlled release fertilizers. In this study, N was applied at 50 kg ha−1 as common ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In rainfed farming, sowing must be carried out at the beginning of the rainy season to ensure adequate water availability and to avoid the negative influence of water deficiency on the plants' metabolic processes. Drought is a major threat to crop production worldwide, and legumes are sensitive to drought stress by negatively affecting BNF, grain yield and protein content in seeds [17]; however, some results have shown that a rate of 50 kg N ha −1 does not impair BNF and can deliver 71% of total N uptake [18]. This is especially relevant in Brazil's agricultural frontiers, such as the specific savanna region (Cerrado) in northeastern Brazil, where there is a lack of site-specific research regarding the use of inoculants and nutrient cycling of organic matter in annual crops.…”
Section: Introductionmentioning
confidence: 99%
“…In rainfed farming, sowing must be carried out at the beginning of the rainy season to ensure adequate water availability and to avoid the negative influence of water deficiency on the plants' metabolic processes. Drought is a major threat to crop production worldwide, and legumes are sensitive to drought stress by negatively affecting BNF, grain yield and protein content in seeds [17]; however, some results have shown that a rate of 50 kg N ha −1 does not impair BNF and can deliver 71% of total N uptake [18]. This is especially relevant in Brazil's agricultural frontiers, such as the specific savanna region (Cerrado) in northeastern Brazil, where there is a lack of site-specific research regarding the use of inoculants and nutrient cycling of organic matter in annual crops.…”
Section: Introductionmentioning
confidence: 99%